Impact of System Quality on User Satisfaction in DJP Online: A Study of Registered Tax Payers at KPP Pratama Jombang - Susilo, Alissa Azizah Herman; Nurhadi, Nurhadi (PT. Riset Press International, 2025)
A well-structured information system plays a crucial role in enhancing the efficiency of digital tax services. In Indonesia, the Directorate General of Taxes (DJP) developed DJP Online to facilitate tax return filing and payment processes. However, user satisfaction with the platform remains a critical concern, primarily influenced by system quality and information quality. This study aims to examine the impact of system quality on user satisfaction with DJP Online, focusing on registered taxpayers at KPP Pratama Jombang. Using a quantitative approach, data were collected through a structured questionnaire from 100 respondents, selected using Slovin’s formula. The data were analyzed using multiple linear regression analysis, along with validity and reliability tests to ensure consistency. The results indicate that system quality significantly influences user satisfaction (R² = 0.67, p < 0.05), with key factors including system reliability, ease of use, and response time. However, some taxpayers reported issues with system accessibility during peak periods. These findings highlight the need for improving system performance to enhance taxpayer compliance. Future research should explore additional variables, such as information quality, trust, and perceived usefulness, to provide a more comprehensive analysis of taxpayer satisfaction with digital tax services.